The Effect of GA3 and NPK Fertilizer on Some Chemical Constituents of Wheat Plant Grain. (Triticum aestivum L.) - AL-Saedi, A. J.H.; AL-Ani, S. S.H.; AL-Arkawizi, A. L. A.; Twaij, S. D. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The experiment was conducted in kalar horticulture station / sulaimania province in growth season in 2006-2007 , by using pots , each pot capacity is 4 kg soil , soil was brought from one of the region fields to study the influence of increasing concentration of GA3(0 , 25, 50, 75 , 100) ppm and two levels of NPK fertilizer (18-18-18) that (0.23 and 0.64) g/4kg soil in perpot (that equals 160 and 320 kg fertilizer /ha.) on some concentration of nutrition elements in grains , the experiment was applied through completely randomized design (C.R.D.) by using three replicates . The results showed that the increase in values of the studied characteristics concentration of (Nitrogen , phosphorus , potassium and percentage of protein ) in grains of wheat with increase in the concentration of GA3 and the level of NPK fertilizer, and the interaction between them as compared with control treatment .